Quantitative and qualitative assessments of a U-shape seating in a large class size: Basis for classroom-level instructional improvement - Masanga, Luisito P. (Animo Repository, 2014)
This research identified the quantitative and qualitative assessments for implementing the U-shape seating arrangement in a large class size specifically for the incoming fourth year students for A Y 2014-2015 in the College of Business Administration. The ratio of the large :lass size in the study was 44 students per teacher. The research study utilized the quantitative and qualitative methods. In the quantitative research aspect, the respondents consisted of 131 students. A survey questionnaire was used to explore the descriptive and inferential problems in the study. The Measures of central tendency and comparisons were used to interpret and analyze the data. In the qualitative method, data from the interview was thematically analyzed. It was tabulated across all co-researchers to get the different concepts. The co-researchers in this study were informed about the role that they are to play in the conduct of the study. The face to face interview was done for a total of 16 co-researchers belonging from the three different fourth year sections. The quantitative findings for the comparative assessments of the fourth year students all highly agreed that the U-shape classroom seating arrangement can promote active class discussion even in a large class size as shown in their composite mean scores of (4.57, 4.53 and 4.58 respectively) with standard deviations of (0.56, 0.61 and 0.60 respectively). There were four statements that showed that the respondents all highly agree in their assessment with U-shape seating arrangement and the following statements were: (1.) U-shape seating arrangement easily facilitates learning (mean scores of 4.71, 4.66 and 4.70 respectively with standard deviations of 0.45, 0.57 and 0.46 respectively). (2.) The teacher can walk in the middle to facilitate discussion (mean scores of 4.87, 4.88 and 4.78 respectively and with standard deviations of 0.33, 0.32 and 0.41 respectively). (3.) The teacher becomes incorporated with the discussion (mean scores of 4.71, 4.52 and 4.58 respectively and standard deviations of 0.45, 0.63 and 0.57 respectively). (4.) It promotes interaction because students face each other while discussing (mean scores of 4.64, 4.59 and 4.72 respectively with standard deviations of 0.45, 0.76 and 0.57 respectively).The qualitative findings on the themes developed why the U-shape seatingarrangement easily facilitates learning: (1.) It promotes listening. (2.) The professor can see the students and prevent sleepiness. (3.) The reporter can easily be understood by the students. (4.) The focus of the student is in the discussion. (4.) You can see the students and professor face to face. (5.) In a U shape it facilitates learning depending on the activity of the professor.Findings regarding themes developed that the teacher can walk in the middle to facilitate discussion: (1.) Feel obligated to listen and pay attention because professor might call them. (2.) The teacher can move in any direction while explaining. (3.) Student does not get bored. (4.) It is advantageous because the professor will not raise their voices and students can hear the professor. Findings regarding themes developed that the teacher becomes incorporated with the discussion. The Professor becomes incorporated with the discussion because he can easily move and walked in the middle of the U shape seating. (1.) His body language and style of talking easily relates to the student hence the student can easily understand the discussion. (2.) Student can easily hear him even at the back. (3.) And he can easily see the faces and reactions of each student. (4.) He becomes acquainted with the student.Findings regarding themes developed that U-shape Seating promotes interaction because students face each other while discussing: (1.) You can see the facial expression of each student especially when reporting. (2.) You can hear the answers and understand the topic. (3.) You will not get bored you will be focused in the reporter. (4.) There are times there is distraction because there is a feeling of shyness when you are facing your classmates or when you answered incorrectly because you are not listening. (5.) It is a challenge in developing self confidence. (6.) Students are encouraged to think because of the critical thinking activity. Findings that showed that were significant differences in the assessments between the male and female students from the different sections of the fourth year regarding the U-shape seating arrangement. The first statement was that, "The U-shape seating arrangement was much better than the traditional desk row seating because it encourages collaboration and active class discussion." The t-value of 3.220 with the corresponding probability value of 0.002 was significant at alpha 0.05. The mean difference of 0.288 was in favor of the male students. This significant difference means that there was sufficient evidence to prove that the male students have higher assessment ratings than their female counterparts that the U-shape seating arrangement is much better than the traditional desk row seating because it encourages collaboration and active class discussion. The second statement was that, "In a U-shape arrangement, the teacher becomes incorporated with the discussion." The t-value of 2.73 with the corresponding probability value of 0.008 was significant at alpha 0.05. The mean difference of 0.277 was in favor again of the male students. This significant difference means that there was sufficient evidence to prove that the male students have higher assessment ratings than their female counterparts toward U-shape arrangement, that the teacher becomes incorporated with the discussion. Findings that showed that there were significant differences in the assessment ratings between the fourth year operations and marketing students regarding the U-shape classroom seating arrangement and the statements are the following: (1.) The U-shape seating arrangement was much better than the traditional desk row seating because it encourages collaboration and active class discussion. The t-value of 2.44 with the corresponding probability value of 0.016 was significant at alpha 0.05. The mean difference of 0.227 was in favor of the marketing students. This significant difference means that there was sufficient evidence to prove that the marketing students have higher assessment ratings in the U-shape seating arrangement than their counterpart. (2.) The second statement was that, "The U-shape arrangement promotes more concentration and listening skills to the students." The t-value of -2-264 with the corresponding probability value of 0.026 was significant at alpha 0.05. The mean difference of -0.26 was in favor of the operations students. This significant difference means that there was sufficient evidence to prove that the operations students have higher assessment rating in the U-shape seating arrangement than the operations student Findings that showed that there were no significant differences on the ages of the students when grouped categorically in all of the variables, the F values were not significant at alpha level of 0.05. This means that there is not enough sample evidences to show that the students differ with one another in terms of their assessment ratings when they are grouped based on their ages. This implies that ages of the students is not an influence to promote active class participation and discussion in a U-shape seating arrangement for a large class size.The contribution of the paper toward classroom-level instructional improvement was to conduct a quantitative and qualitative assessments for implementing the U-shape seating arrangement in a large class size specifically for the incoming fourth year students for A y 2014-2015 in the College of Business Administration. The following are the basis for implementation:: (1.) The U-shape seating arrangement is very effective in group reporting because of the strategic location of the professor (in the middle when lecturing) and the students (when they are reporting). At this location, the professor can see the faces of the students, preventing some students from getting sleepy and bored thus acquiring their attention to listen. On the other hand, the reporters can be seen easily by the students hence creating an opportunity for them to pay close attention to the reporters. In short i(2.) The U-shape seating is effective when the professor will walk around in the middle while discussing because it projects his voice audible to students even at the back. Furthermore, it has a behavioral impact to the students because of the risk of being called or questioned by the professor and creates discipline from preventing students from being bored and sleepy 3.) The U-shape seating is very effective for whole-class discussion because it was supplemented with a critical-thinking activity by the professor. Since the students can see each other' faces including the teacher, there are no students that can hide even at the back and avoid participation. This means that U-shape encourages active participation from students and enhances their oral communication and cognitive skills. The recommendations of the study are the following: (1.) U-Shape seating arrangement in a large class size should be supplemented by group reporting activity to promote active class discussion. (2.) The front and second rows of the seats should have a distance of at least one meter to allow movement of the students and professor. (3.) The professor should walk in the middle during discussion to create discipline and behavioral impact in promoting active listening of the students. (4.) Professor should always maintain eye to eye contact with the students when walking in the middle and should ask questions to students related to the topic to avoid the boredom and feeling of being sleepy. (5.) It is very imperative that professor should exercise critical thinking activity during class discussion. The professor can use an index card for random "cold calling' of students names for graded class recitation. (6.) Professor should have a student seating plan arrange in a U-shape. (7.) U-shape seating is arrange before the start of the class and should be re-arranged to the traditional row seating after the class. (8.) Do not use U-shape seating for activities such as quizzes and major exams. The traditional row seating is recommended. In future study, it is recommended to have an action research that will enhance more critical thinking activities in a U-Shape seating arrangement for a large class size.